2003
DOI: 10.2172/15004496
|View full text |Cite
|
Sign up to set email alerts
|

Physical Property and Rheological Testing of Actual Transuranic Waste from Hanford Single-Shell Tanks

Abstract: (PNNL) to measure the composites' physical properties. These tank composites were prepared from core samples retrieved from these tanks. These composites may not be representative of the entire contents of the tank, but they provide some indication of the properties of the waste in these underground storage tanks. Dilutions in water were also prepared from these composite samples. The measurements included paint filter tests, viscosity, direct measurement of shear strength with a rheometer, settling and centri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…The core composites for these tanks were composed of re-hydrated samples from storage . The typical total fractional water content in the as-received samples used to make the composites of Tingey et al (2003) was approximately 0.80 by mass (Rassat et al 2003). To achieve the lowest UDS mass concentration reported in Poloski et al (2006) for the undiluted composite with this water content, T-204 at 0.17 (Figure 3.80), the concentration of water in the liquid must be approximately 0.95 by mass.…”
Section: Shear Strength-uds Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The core composites for these tanks were composed of re-hydrated samples from storage . The typical total fractional water content in the as-received samples used to make the composites of Tingey et al (2003) was approximately 0.80 by mass (Rassat et al 2003). To achieve the lowest UDS mass concentration reported in Poloski et al (2006) for the undiluted composite with this water content, T-204 at 0.17 (Figure 3.80), the concentration of water in the liquid must be approximately 0.95 by mass.…”
Section: Shear Strength-uds Concentrationmentioning
confidence: 99%
“…Hanford waste shear-strength and UDS-concentration data for core composites and dilutions thereof (see Tingey et al 2003) There may be discrepancy in the measured composite UDS concentration and that estimated for in situ conditions for these B-203, T-204, and T-203 measurements. The core composites for these tanks were composed of re-hydrated samples from storage .…”
Section: Shear Strength-uds Concentrationmentioning
confidence: 99%
“…The model assumed (e.g., Bingham and Casson) for the data to extrapolate to zero strain rate can also affect the results (Nguyen and Boger 1992;Chhabra 1992). The data presented in Tingey et al (2003) demonstrate for those Hanford wastes they considered that the waste has overshoot behavior, resulting in under-prediction of the yield point if the traditional models are applied.…”
Section: Couette Viscometermentioning
confidence: 99%
“…As noted in Tingey et al (2003), the extrusion scale may be expected to affect the results. The current range of applicability of the methodologies is also limited to 3.3 shear strengths on the order of 10,000 Pa (maximum simulant shear strength employed by Gauglitz and Aiken [1997] was 6,500 Pa).…”
Section: Waste Core Extrusion Behaviormentioning
confidence: 99%
“…Gauglitz et al (2009) reported comparisons for Hanford sludge waste. The ratio of shear strength to Bingham yield stress for diluted B-203 and T-203 waste is 5 and 8, respectively (Tingey et al 2003). A ratio approaching 1000 may be determined from core-sample analyses of AZ-101 waste (Urie et al 2002).…”
Section: Rheologymentioning
confidence: 99%